PROFIL BIOAUTOGRAM AKTIVITAS ANTIBAKTERI EKSTRAK ISOLAT JAMUR LAUT PADA ALGAE Kappaphycus alvarezii SECARA KLT BIOAUTOGRAFI - Fitriana Fitriana; Rusli Rusli (As-Syifaa Jurnal Farmasi, 2017)
The Research Chromatogram Profile Of Activities Antibacterial Extracts Isolates Marine Fungi in Algae Kappaphycus alvarezii by TLC Bioautography has been done with the intention of doing the screening test of pathogenic bacteria that can be inhibited by the extract of F3 (extract liquid culture and extract mycelia) and extracts of E (extract liquid culture and extract mycelia ) and see chromatogram profile of liquid culture extract of F3 on bacteria Escherichia coli and mycelia extract of E on bacteria Bacillus subtilis. This research was conducted purification of Fungi isolates E and F3 followed by fermentation process of fungi isolates for 3 weeks. Then proceed with the extraction process using an ethyl acetate solvent. The solvent was evaporated to obtain a dry extract, followed by a screening test of antibacterial activity against bacterial pathogenic, antibacterial activity test by TLC Bioautography to liquid culture extract of F3 and extract mycelia of E. The results of the screening test with a concentration of 250 µg was obtained to extract liquid culture of F3 and E provide activity against 5 pathogenic bacteria to extract mycelia while F3 and E provide activity against two bacterial pathogens. Separation of compounds by TLC using the ethyl acetate eluent: ethanol: water (8: 2: 1). The result of TLC Bioautography test of liquid culture extract of F3 to bacteria Escherichia coli and mycelia extract of E on bacteria Bacillus subtilis showed the existence of antibacterial activity.